2018
DOI: 10.1242/jcs.220202
|View full text |Cite
|
Sign up to set email alerts
|

Misfolding-prone proteins are reversibly sequestered to an Hsp42-associated granule upon chronological aging

Abstract: Alteration of protein localization is an important strategy for cells to regulate protein homeostasis upon environmental stresses. In the budding yeast , many proteins relocalize and form cytosolic granules during chronological aging. However, the functions and exact components of these protein granules remain uncharacterized in most cases. In this study, we performed a genome-wide analysis of protein localization in stationary phase cells, leading to the discovery of 307 granule-forming proteins and the ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 77 publications
4
22
0
Order By: Relevance
“…It was also demonstrated that under carbon starvation, Hsp42-SPGs co-immunoprecipitates with Ssa1-TAP and not Hsp42-TAP (Lee et al, 2018). This may indicate that under carbon starvation stress, Hsp42 is predominantly insoluble, while Ssa1 (Shiber et al, 2013) and the other SPG components (Lee et al, 2018), similar to PSGs (Enenkel, 2018), are soluble. Taken together, these results imply that Hsp42 may preferentially sequester insoluble proteins.…”
Section: The Role Of Small Heat Shock Proteins In Facilitating Granulmentioning
confidence: 96%
See 4 more Smart Citations
“…It was also demonstrated that under carbon starvation, Hsp42-SPGs co-immunoprecipitates with Ssa1-TAP and not Hsp42-TAP (Lee et al, 2018). This may indicate that under carbon starvation stress, Hsp42 is predominantly insoluble, while Ssa1 (Shiber et al, 2013) and the other SPG components (Lee et al, 2018), similar to PSGs (Enenkel, 2018), are soluble. Taken together, these results imply that Hsp42 may preferentially sequester insoluble proteins.…”
Section: The Role Of Small Heat Shock Proteins In Facilitating Granulmentioning
confidence: 96%
“…Attempts to identify additional proteins that aggregate similarly to PSGs, and might form a PSG scaffold, were described in two independent studies. Both used an arrayed GFP clone collection of S. cerevisiae tagged open reading frames (Huh et al, 2003) to systematically follow the reorganization of yeast proteins under carbon starvation (Gu et al, 2017;Lee et al, 2018). Other than Ubi4, Ubp6, Blm10 and the proteasome subunits themselves, none of the detected protein aggregates were reversable upon carbon addition, or co-localized with PSGs (Gu et al, 2017;Lee et al, 2018).…”
Section: Proteasome Homeostasis During Carbon Deprivationmentioning
confidence: 99%
See 3 more Smart Citations